A microwave absorption/transmission integrated sandwich structure based on composite corrugation channel: Design, fabrication and experiment. (1st December 2019) - Jiang, Wei; Ma, Hua; Yan, Leilei; Wang, Jiafu; Han, Yajuan; Zheng, Lin; Qu, Shaobo
Abstract: A microwave absorption/transmission integrated sandwich structure (MATSS) with excellent mechanical properties was proposed and investigated in this paper. This structure is composed of composite corrugation panels with foams filled in its channels. The absorption/transmission property is produced based on the mechanism of spatial dispersion engineering and electromagnetic resonance. Different from previous designs, this proposal can realize a broadband absorption (5.74–7.84 GHz) below transmission band (8.96–12.45 GHz) with the absorptivity and transmissibility more than 80%. Moreover, compressive experiment results show that filling foams in channels can obviously improve the mechanical properties of this structure. The peak compressive strength of the foam-filled MATSS can reach to 25.21 MPa with a core density 0.32 g/cm 3, which are more competitive comparing with many metallic sandwich core topologies.